1986
DOI: 10.1172/jci112637
|View full text |Cite
|
Sign up to set email alerts
|

Shared idiotypes and restricted immunoglobulin variable region heavy chain genes characterize murine autoantibodies of various specificities.

Abstract: The study of the Ig variable region heavy chain (VH) genes used to encode antibodies specific for self-epitopes from murine hybridomas showed that three VH families are primarily utilized: VH J558, the largest family, and VH QPC52 and VH 7183, the families most proximal to the Ig joinin region heavy chain genes. These monoclonal autoantibodies express cross-reactive idiotopes shared by rheumatoid factors and antibodies specific for Sm. The expression of these idiotypes is independent of major histocompatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

1987
1987
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 32 publications
3
40
1
Order By: Relevance
“…It has been previously demonstrated that the VH gene families most proximal to the D region locus rearrange frequently in B lymphocytes from fetal or neonatal mice as well as in pre-B lymphocyte lines [24,25], in contrast to adult mature B cells which utilize VH gene families at frequencies that correlate with family size [26]. In natural autoantibodies a similar biased utilization of VH gene families proximal to the D region locus has been reported by several investigators [27][28][29], but has not been confirmed by others [2,7,30]. Our observation that all five anti-mouse erythrocyte MoAbs are encoded by members of the 5' most proximal VH gene families further argues against the preferential rearrangement of VH families proximal to the D regions for the generation of autoantibodies, and is in agreement with previous studies of anti-mouse erythrocyte autoantibodies [9,10].…”
Section: Dtscusstonsupporting
confidence: 71%
“…It has been previously demonstrated that the VH gene families most proximal to the D region locus rearrange frequently in B lymphocytes from fetal or neonatal mice as well as in pre-B lymphocyte lines [24,25], in contrast to adult mature B cells which utilize VH gene families at frequencies that correlate with family size [26]. In natural autoantibodies a similar biased utilization of VH gene families proximal to the D region locus has been reported by several investigators [27][28][29], but has not been confirmed by others [2,7,30]. Our observation that all five anti-mouse erythrocyte MoAbs are encoded by members of the 5' most proximal VH gene families further argues against the preferential rearrangement of VH families proximal to the D regions for the generation of autoantibodies, and is in agreement with previous studies of anti-mouse erythrocyte autoantibodies [9,10].…”
Section: Dtscusstonsupporting
confidence: 71%
“…Moreover, with few exceptions (37), autoantibodies seem to arise from the same genetic repertoire that encodes antibodies directed against exogenous antigens (34). The slight restriction for most 3' VH families (7183 and Q52) found for several autoantibodies (38,39) seems to correspond to a preferential rearrangement in normal pre-B cells (40) and to reflect the VH gene distribution in the total repertoire of normal mice (41). Our present results confirm the observation that autoantibodies and antibodies to exogenous antigens can be encoded by the same germ-line genes.…”
Section: E S G V P D R F T 0 S C S 0 T D F T L T I S S V Q a E D Lmentioning
confidence: 99%
“…Indeed, it has beeen demonstrated that members of VH gene families localized most proximal to the D region locus (VH7183 and Q52) rearranged more frequently in B cells from fetal or neonatal mice or in pre-B cell lines [17], than in mature B cells which expressed VH gene families at a frequency related to the family size. The genetic origin of autoantibodies in the adult mouse has shown biased [18][19][20] and unbiased utilization of 3'-proximal VH gene families [21]. Analysis of the selection of autoantibody V genes during autoimmunity depends upon the assessment of the linkage of the autoantibodies to the pathogenic process.…”
Section: Discussionmentioning
confidence: 99%